2017
DOI: 10.1016/j.cherd.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Process design and economic evaluation of green extraction methods for recovery of astaxanthin from shrimp waste

Abstract: Sunflower oil (SF) and its methyl ester as well as supercritical fluid (SC-CO2+ 5 wt% EtOH) have recently been shown as potential green solvents which could substitute traditional organic solvents. This study investigates the economic feasibility of using these green solvents to extract astaxanthin (ASX) from shrimp processing waste. The feasibility of commercial use of the green solvents under plausible process conditions is compared to extraction with a mixture of hexane: isopropanol (Hex:IPA). The process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In addition to chitin, shrimp waste also contains several bioactive compounds, such as astaxanthin, amino acids, and fatty acids [92,93,94,95,96,97,98,99,100,101]. These bioactive compounds have a wide range of applications, including those in the medical, therapeutic, cosmetic, paper, pulp, and textile industries, as well as in biotechnology and food [95,96,97,98,99,100,101,102,103,104]. Pacheco et al [95] recovered chitin and astaxanthin from shrimp waste that was fermented using lactic acid bacteria, while Parjikolaei et al [99] designed a green extraction method using sunflower oil to recover astaxanthin from shrimp waste.…”
Section: Use Of Shrimp and Crab Processing Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chitin, shrimp waste also contains several bioactive compounds, such as astaxanthin, amino acids, and fatty acids [92,93,94,95,96,97,98,99,100,101]. These bioactive compounds have a wide range of applications, including those in the medical, therapeutic, cosmetic, paper, pulp, and textile industries, as well as in biotechnology and food [95,96,97,98,99,100,101,102,103,104]. Pacheco et al [95] recovered chitin and astaxanthin from shrimp waste that was fermented using lactic acid bacteria, while Parjikolaei et al [99] designed a green extraction method using sunflower oil to recover astaxanthin from shrimp waste.…”
Section: Use Of Shrimp and Crab Processing Byproductsmentioning
confidence: 99%
“…These bioactive compounds have a wide range of applications, including those in the medical, therapeutic, cosmetic, paper, pulp, and textile industries, as well as in biotechnology and food [95,96,97,98,99,100,101,102,103,104]. Pacheco et al [95] recovered chitin and astaxanthin from shrimp waste that was fermented using lactic acid bacteria, while Parjikolaei et al [99] designed a green extraction method using sunflower oil to recover astaxanthin from shrimp waste. Amado et al [96] reported on the recovery of high concentrations of astaxanthin by the ultrafiltration of wastewater used to cook shrimp and indicated that astaxanthin is associated with retained proteins that have a high molecular weight.…”
Section: Use Of Shrimp and Crab Processing Byproductsmentioning
confidence: 99%
“…In a solvent extraction process, the main task is to find the most suitable solvent to extract the phytochemicals of interest from the raw vegetable material [16][17][18]. However, during the early stages of the extraction process, experiment-based methods are usually employed to select the best performing solvent from a preselected shortlist [19], which implies spending, reagents, time, human resources, and installed capacity, among other resources.…”
Section: Cga Solid-liquid Extraction Processmentioning
confidence: 99%
“…Other studies reported that doses of 3 mg/kg, over an eight-week treatment period, reduced retinal oxidative stress and inflammatory mediators in rats with streptozotocin-induced diabetes [ 15 ]. The utilization of AST, as a promising therapeutic strategy in ocular disease and in particular in diabetic retinopathy, requires the use of AST extracted using “green” methods, as an alternative to traditional chemical methods that use toxic solvents [ 16 ]. The “green techniques” are based on the discovery and design of extraction processes that reduce energy consumption, allow the use of alternative solvents and renewable natural products, and ensure a safe and high-quality extract/product [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%